Interpreting the industry 4.0 future: technology, business, society and people. Issue 3 (26th January 2021) - Schiele, Holger; Bos-Nehles, Anna; Delke, Vincent; Stegmaier, Peter; Torn, Robbert-Jan
Abstract : Purpose: Industrial revolutions have been induced by technological advances, but fundamentally changed business and society. To gain a comprehensive understanding of the fourth industrial revolution (I4.0) and derive guidelines for business strategy, it is, therefore, necessary to explore it as a multi-facet phenomenon. Most literature on I4.0, however, takes up a predominantly technical view. This paper aims to report on a project discussing a holistic view on I4.0 and its implications, covering technology, business, society and people. Design/methodology/approach: Two consecutive group discussions in form of academic world cafés have been conducted. The first workshop gathered multi-disciplinary experts from academia, whose results were further validated in a subsequent workshop including industry representatives. A voting procedure was used to capture participants perspectives. Findings: The paper develops a holistic I4.0 vision, focusing on five core technologies, their business potential, societal requests and people implications. Based on the model a checklist has been developed, which firms can use a tool to analyze their firm's situation and draft their industry 4.0 business strategy. Originality/value: Rather than focusing on technology alone – which by itself is unlikely to make up for a revolution – this research integrates the entire system. In this way, a tool-set for strategy design results.